(untitled) (Communications in Computational Physics, 2020)
The mechanism of jet flow expanding into vacuum environment (or extremely low density environment) is important for the propulsion unit of micro-electro-mechanical systems (MEMS), the thruster of spacecraft, the attitude control system of satellite, etc.. Since its flow field is often composed of local continuum region and local rarefied region, the jet flow into vacuum has noteworthy multi-scale transportation behaviors. Therefore, the numerical study of such flows needs the multi-scale schemes which are valid for both continuum and rarefied flows. In the past few years, a series of unified methods for whole flow regime (from continuum regime to rarefied regime) have been developed from the perspective of the direct modeling, and have been verified by sufficient test cases. In this paper, the compressible conserved discrete unified gas-kinetic scheme is further developed and is utilized for predicting the jet flows into vacuum environment. In order to cover the working conditions of both aerospace and MEMS applications, the jet flows with a wide range of inlet Knudsen (Kn) numbers (from 1E-4 to 100) are considered. The evolution of flow field during the entire startup and shutdown process with Kn number 100 is predicted by the present method, and it matches well with the result of analytical collisionless Boltzmann equation. For Kn numbers from 1E-4 to 10, the flow field properties such as density, momentum, and pressure are investigated, and the results are provided in details, since the published results are not sufficient at the present stage. The extent and intensity of the jet flow influence are especially investigated, because they are strongly related to the plume contamination and momentum impact on objects facing the jet, such as the solar paddles which face the attitude control thruster during the docking process.